Composite bamboo charcoal dispersoid for viscose fibers as well as preparation method and application of composite bamboo charcoal dispersoid
By using composite bamboo charcoal dispersions coated with metal oxides and silica in textiles, the problem of low deodorization efficiency of textiles in strong acid and alkali environments is solved, and the antibacterial deodorization performance and spinning stability of fibers are improved.
Patent Information
- Application Number
- CN202411263446.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-10
- Publication Date
- 2025-01-17
- Estimated Expiration
- 2044-09-10
AI Technical Summary
The adsorption and deodorization materials of existing textiles are inefficient in strong acid and alkali environments and their particle size is not suitable for the spinning process, resulting in limited fiber spinning.
Using composite bamboo charcoal dispersion, the first and second covers are formed by covering metal oxides and silica on the surface of bamboo charcoal particles, thereby enhancing the adsorption and odor removal ability, and through surfactant during spinning. Improve dispersion and stability.
It improves the antibacterial deodorization performance of the fiber, enhances the adsorption capacity of ammonia, acetic acid and isovaleric acid, reduces the loss of metal oxides, and ensures stability and deodorization efficiency during spinning.
Abstract
Description
Technical Field
[0001] The invention belongs to the field of textile fibers, and in particular relates to a composite bamboo charcoal dispersion for viscose fibers and a preparation method and application thereof. Background Art
[0002] As people's living standards improve, consumers have higher and higher functional requirements for textiles, including antibacterial, deodorizing, flame retardant, far infrared, etc., especially for fabrics that are in close contact with the human body.
[0003] Bamboo charcoal has a high specific surface area and rich pore structure, making it an ideal adsorption and deodorization material. Especially after modification, it has a large adsorption capacity and deodorization function for odors such as ammonia and hydrogen sulfide. However, the deodorization efficiency of single bamboo charcoal is low, and the deodorization rate is often low due to deodorization saturation, or even odor re-release.
[0004] Currently commonly used inorganic deodorants such as zinc oxide and silicate have good deodorizing effects. Silicate mineral extracts have good chemical stability, good swelling properties, high negative charge and excellent ion exchange properties, and are effective against sweat odor components such as acetic acid, isovaleric acid and ammonia. The photocatalytic effect of zinc oxide can achieve a lasting chemical elimination effect on odor, but the viscose fiber spinning process has a strong acid and alkali environment, which puts higher requirements on the acid and alkali resistance of the deodorant.
[0005] Patent application No. 201410250425.8 dissolves bamboo charcoal nano-slurry from the back and adds it to the denatured viscose and stirs it evenly. The sustained-release capsules made of aluminosilicate powder are added before spinning by pre-spinning injection, which avoids the serious loss of aluminosilicate in strong acid and alkali in application No. 201210349910.1, and achieves the purpose of long-lasting antibacterial and deodorization. However, the particle size of the microcapsule reaches 2-4 microns, which limits the spinnability of the fiber.
[0006] Patent application number 202211296447.9 adopts a special composite hybrid treatment of zinc pyrithione and zinc oxide, which improves the shortcomings of zinc pyrithione's alkali resistance and zinc oxide's acid resistance. The improved organic zinc antibacterial slurry has good tolerance in strong acid and alkali environments, but its particle size distribution is 1-2 microns, which leads to the limited spinnability of its fibers. Summary of the invention
[0007] The present invention aims to overcome the defects of the adsorption and deodorization materials used for textiles in the prior art that they cannot directly withstand strong acid and strong alkali environments, resulting in low deodorization efficiency and their particle size is not suitable for the spinning process. A composite bamboo charcoal dispersion for viscose fiber and its preparation method and application are provided to overcome the above-mentioned shortcomings.
[0008] To solve the above shortcomings, this application is implemented through the following technical solutions: In a first aspect, the present invention first provides a composite bamboo charcoal dispersion for viscose fibers. It includes composite bamboo charcoal, surfactant and water; wherein, The composite bamboo charcoal comprises bamboo charcoal particles, the outside of which is coated with a first coating containing at least one metal oxide, and the outside of the first coating is coated with a second coating composed of silicon dioxide.
[0009] Compared with traditional bamboo charcoal, the composite bamboo charcoal dispersion in the present application has a first coating and a second coating on its surface, so that it has better adsorption and removal effects on odors such as ammonia and hydrogen sulfide.
[0010] Specifically, the first coating contains metal oxides, so these metal oxides can react with organic acids such as acetic acid and isovaleric acid to achieve chemical adsorption of such substances. At the same time, metal oxides usually also have a certain photocatalytic effect, so this part of the photocatalytic effect can be used to degrade odor into non-toxic and odorless substances.
[0011] Combined with the actual operating environment that the composite bamboo charcoal dispersion in the present application needs to face during the application process, the composite bamboo charcoal dispersion in the present application is applied to the field of viscose fiber textiles. During the application process, the viscose stock solution is alkaline, and during the spinning process of viscose fiber, the composite bamboo charcoal dispersion needs to be mixed with the viscose stock solution and then coagulated in an acidic coagulation bath. After the coagulation, alkaline washing and other steps are required. Therefore, during the spinning process, the metal oxides in the composite bamboo charcoal dispersion need to face multiple environments with different acid and alkaline conditions. However, metal oxides are generally not resistant to acid and alkaline environments, so the addition of a single metal oxide cannot provide a guarantee for the adsorption and deodorization of textiles.
[0012] In view of the above problems, the applicant has coated the first coating with a second coating composed of silicon dioxide, which can effectively block the corrosion of the acidic viscose stock solution to the metal oxide during the spinning process, thereby reducing the loss rate of the metal oxide. In addition, silicon dioxide itself has a certain adsorption effect, and its distribution on the surface of the metal oxide can also enhance the adsorption of ammonia, acetic acid, and isovaleric acid, so that the first coating and the second coating play a synergistic role.
[0013] Preferably, the mass concentration of the composite bamboo charcoal is 20-45%.
[0014] Preferably, the mass of the first coating body is 1-5% of the mass of the bamboo charcoal particles; The mass of the second coating body is 1-5% of the mass of the bamboo charcoal particles.
[0015] The applicant found in the experiment that the weight of the first coating and the second coating has an important influence on the performance of the composite bamboo charcoal dispersion. For the first coating, the applicant found that when the weight of the first coating is low, the antibacterial and deodorizing effect of the fiber is not significantly improved, and when the weight is too high, the size of the composite bamboo charcoal will be too high, and it is also easy to block the porous structure of the bamboo charcoal particles, so that the adsorption efficiency of the odor cannot be further improved. For the second coating, when the weight of the second coating is less, the thickness of its coating layer is low and not dense enough, so that the metal oxide will flow out and lose during the application process, resulting in a decrease in the adsorption efficiency of the odor, and when the weight of the second coating is more, its reaction speed during the deposition process is faster, resulting in a large volume of the coating, unable to achieve good composite with the fiber, and easy to fall off from the fiber. Therefore, in the present application, by setting the mass of the first coating to 1-5% of the mass of the bamboo charcoal particles and the mass of the second coating to 1-5% of the mass of the bamboo charcoal particles, a good composite effect on the fiber can be achieved under the premise of effectively adsorbing odor.
[0016] Preferably, the metal oxide in the first coating includes at least one or more oxides of transition metal elements.
[0017] Transition metal oxides usually have rich chemical activity and can react chemically with a variety of odor molecules, thereby achieving more efficient adsorption. At the same time, the surface of transition metal oxides usually has a high density of active sites, which can adsorb more odor molecules. Compared with other types of metal oxides, transition metal oxides have certain advantages in adsorption performance. In addition, transition metal oxides have high electron affinity and active sites, and their adsorption ability is also strong, which can effectively adsorb reactants and products and increase the reaction rate. In addition, since transition metal oxide catalysts have high catalytic activity, the required reaction temperature and pressure are often lower, which is more economical and environmentally friendly than other catalysts. In addition, transition metal oxide catalysts have good stability, and their stability is often higher than other catalysts. Due to their high redox ability, electron affinity and adsorption ability, they can effectively resist unstable factors in the catalytic process. At the same time, since most transition metal oxide catalysts have high specific surface area and porosity, they can be effectively dispersed in the reaction system, making their catalytic activity more stable. Finally, some transition metal oxides, such as copper oxide and zinc oxide, have certain antibacterial properties. Applying these metal oxides to composite bamboo charcoal can make viscose fiber have antibacterial function and improve the hygienic performance of the product.
[0018] Preferably, the metal oxide in the first coating body further comprises one or more oxides of main group metal elements; The mass ratio of the oxide of the transition metal element to the oxide of the main group metal element is 10:(1-5).
[0019] The inventors of the present application found in actual testing that if the metal oxide in the first coating contains oxides of certain main group metal elements in addition to oxides of transition metal elements, the adsorption and removal effect of the first coating on odor molecules can be further enhanced.
[0020] First, oxides of transition metal elements and oxides of main-group metal elements often have different adsorption mechanisms. Transition metal oxides usually remove odor molecules through chemical adsorption and catalysis, while main-group metal oxides may rely more on physical adsorption or forming specific chemical bonds with specific molecules. The combination of the two can achieve complementary adsorption effects and improve the adsorption capacity of different types of odor molecules.
[0021] Secondly, the oxides of main group metal elements can adsorb some odorous substances that are difficult to adsorb by transition metal oxides, thereby expanding the adsorption range of composite bamboo charcoal. For example, some main group metal oxides have a strong adsorption effect on polar molecules, while transition metal oxides may be more effective for non-polar molecules.
[0022] Finally, the main group metal oxide may form a stable complex with the transition metal oxide to improve the structural stability of the first coating body. This stability can prevent the coating body from decomposing or falling off during use, thereby ensuring the long-term adsorption performance of the composite bamboo charcoal.
[0023] Preferably, the oxide of the transition metal element includes any one or more of zinc oxide, titanium dioxide, silver oxide, and copper oxide; The oxide of the main group metal element includes any one or more of magnesium oxide, aluminum oxide and tin oxide.
[0024] Preferably, the surfactant includes an ionic surfactant and a non-ionic surfactant; The mass concentration of the ionic surfactant is 1-5%, and the mass concentration of the non-ionic surfactant is 1-8%.
[0025] In the present application, two different surfactants are added to the composite bamboo charcoal dispersion for viscose fiber. The reason is that the two dispersants, ionic surfactant and non-ionic surfactant, can play a dual role of synergistically improving dispersibility and enhancing stability.
[0026] To improve dispersibility synergistically: Ionic surfactants are adsorbed on the surface of particles through the electrostatic effect between ions, so that the particles have the same charge, thereby generating electrostatic repulsion and preventing the particles from aggregating. Non-ionic surfactants mainly form a stable protective film on the surface of particles through the steric effect to prevent the particles from approaching each other. The two surfactants have different mechanisms of action, and the synergistic effect can more effectively improve the dispersibility of composite bamboo charcoal in water. Different types of surfactants have different adaptability to particles and media of different properties. Using two surfactants at the same time can expand the scope of application of the dispersion system and ensure that good dispersion effects can be achieved under different environmental conditions.
[0027] To enhance stability: The ionic surfactant and non-ionic surfactant work together to provide dual protection for the composite bamboo charcoal particles. The electrostatic repulsion generated by the ionic surfactant and the steric hindrance effect formed by the non-ionic surfactant complement each other, making the particles more stable in the dispersed system and less prone to precipitation or agglomeration. In addition, in practical applications, the dispersed system may be affected by various external factors, such as temperature changes, pH fluctuations, the presence of electrolytes, etc. The synergistic effect of the two surfactants can enhance the resistance of the dispersed system to these external factors and maintain the dispersion stability of the composite bamboo charcoal.
[0028] Preferably, the ionic surfactant includes one or more of sodium dodecylbenzene sulfonate, sodium lignin sulfonate, naphthalene sulfonate formaldehyde condensate, and sodium polycarboxylate; The nonionic surfactant includes one or more of polysorbate, fatty alcohol polyoxyethylene ether, phenylphenol polyoxyethylene ether, castor oil polyoxyethylene ether, and fatty amine polyoxyethylene ether.
[0029] In a second aspect, the present invention further provides a method for preparing the composite bamboo charcoal dispersion for viscose fiber, comprising the following steps: (S.1) dispersing the surfactant and bamboo charcoal particles in deionized water, and wet-grinding to obtain nano bamboo charcoal slurry; (S.2) adjusting the pH of the nano bamboo charcoal slurry to alkaline, adding a metal salt compound, and reacting to coat the surface of the bamboo charcoal particles with a first coating body; (S.3) continuing to add a silicon dioxide precursor to the reaction solution to react, thereby coating the second coating body outside the first coating body; (S.4) washing and drying the generated precipitate to obtain composite bamboo charcoal; (S.5) The composite bamboo charcoal, surfactant and water are mixed evenly and then ground in a grinder to obtain a composite bamboo charcoal dispersion for viscose fiber.
[0030] In a third aspect, the present invention also provides the use of the composite bamboo charcoal dispersion for viscose fibers as described above in the preparation of textile fibers.
[0031] Therefore, the present invention has the following beneficial effects: The present invention modifies bamboo charcoal by metal oxide and silicon dioxide, thereby obtaining composite bamboo charcoal, and then grinding and dispersing with surfactant and deionized water to obtain composite bamboo charcoal dispersion. The molecular structure of the treated and modified composite bamboo charcoal contains silicon dioxide, metal oxide and bamboo charcoal. The metal oxide is firstly compounded with bamboo charcoal particles, and then a dense protective film is formed by the deposition of silicon dioxide, thereby avoiding the loss of metal oxide in a strong acid and alkali environment. Among them, bamboo charcoal has a large specific surface area and pore structure, and is an excellent natural antibacterial and deodorizing material. Silicon dioxide has a certain adsorption effect, and it is distributed on the fiber surface, and can also enhance the adsorption effect on ammonia, acetic acid and isovaleric acid. Metal oxide has a physical adsorption effect on organic acid, and can also utilize photocatalysis to degrade odor into non-toxic and odorless substances, and utilize chemical adsorption to achieve a deodorizing effect. DETAILED DESCRIPTION
[0032] The present invention is further described below in conjunction with specific embodiments. Those of ordinary skill in the art will be able to implement the present invention based on these descriptions. In addition, the embodiments of the present invention involved in the following description are generally only embodiments of a part of the present invention, rather than all embodiments. Therefore, based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work should fall within the scope of protection of the present invention.
[0033] Example 1 A composite bamboo charcoal dispersion for viscose fiber, the preparation method of which is as follows: (S.1) Add 3 g of sodium dodecylbenzene sulfonate to 67 g of deionized water, mix at 500 rpm, add 30 g of bamboo charcoal, stir at 1000 rpm for 1 hour, grind in a grinder for 2 hours, and use a laser particle size analyzer to measure the particle size D90 < 0.3 μm to obtain nano bamboo charcoal slurry.
[0034] (S.2) The pH value of the nano bamboo charcoal slurry is adjusted to 9 with 1 mol / L sodium hydroxide solution, the temperature is raised to 55°C, 1 mol / L zinc sulfate solution is added, the temperature is raised to 120°C for hydrothermal reaction for 10 hours, and the amount of zinc sulfate solution added is 1% of the bamboo charcoal calculated as zinc oxide.
[0035] (S.3) Then the temperature is lowered to 70°C, 1 mol / L sodium silicate solution is added, and the reaction is carried out for 1 hour. The amount added is 1% of the bamboo charcoal in terms of silicon dioxide.
[0036] (S.4) The precipitate is washed with deionized water for multiple times, filtered, and dried to obtain composite bamboo charcoal.
[0037] (S.5) 30 g of the composite bamboo charcoal, 1 g of naphthalenesulfonate formaldehyde condensate and 5 g of fatty alcohol polyoxyethylene ether are mixed at high speed to obtain a composite bamboo charcoal dispersion.
[0038] Example 2 A composite bamboo charcoal dispersion for viscose fiber, the preparation method of which is as follows: (S.1) Add 3 g of sodium dodecylbenzene sulfonate to 67 g of deionized water, mix at 500 rpm, add 30 g of bamboo charcoal, stir at 1000 rpm for 1 hour, grind in a grinder for 2 hours, and use a laser particle size analyzer to measure the particle size D90 < 0.3 μm to obtain nano bamboo charcoal slurry.
[0039] (S.2) The pH value of the nano bamboo charcoal slurry is adjusted to 9 with 1 mol / L sodium hydroxide solution, the temperature is raised to 55°C, 1 mol / L zinc sulfate solution is added, the temperature is raised to 120°C for hydrothermal reaction for 10 hours, and the amount of zinc sulfate solution added is 2% of the bamboo charcoal based on zinc oxide.
[0040] (S.3) Then the temperature is lowered to 70°C, 1 mol / L sodium silicate solution is added, and the reaction is carried out for 1 hour. The amount added is 3% of the bamboo charcoal in terms of silicon dioxide.
[0041] (S.4) The precipitate is washed with deionized water for multiple times, filtered, and dried to obtain composite bamboo charcoal.
[0042] (S.5) 30 g of the composite bamboo charcoal, 1 g of naphthalenesulfonate formaldehyde condensate and 5 g of fatty alcohol polyoxyethylene ether are mixed at high speed to obtain a composite bamboo charcoal dispersion.
[0043] Example 3 A composite bamboo charcoal dispersion for viscose fiber, the preparation method of which is as follows: (S.1) Add 3 g of sodium dodecylbenzene sulfonate to 67 g of deionized water, mix at 500 rpm, add 30 g of bamboo charcoal, stir at 1000 rpm for 1 hour, grind in a grinder for 2 hours, and use a laser particle size analyzer to measure the particle size D90 < 0.3 μm to obtain nano bamboo charcoal slurry.
[0044] (S.2) The pH value of the nano bamboo charcoal slurry is adjusted to 9 with 1 mol / L sodium hydroxide solution, the temperature is raised to 55°C, 1 mol / L zinc sulfate solution is added, the temperature is raised to 120°C for hydrothermal reaction for 10 hours, and the amount of zinc sulfate solution added is 5% of the bamboo charcoal based on zinc oxide.
[0045] (S.3) Then the temperature is lowered to 70°C, 1 mol / L sodium silicate solution is added, and the reaction is carried out for 1 hour. The amount added is 5% of the bamboo charcoal in terms of silicon dioxide.
[0046] (S.4) The precipitate is washed with deionized water for multiple times, filtered, and dried to obtain composite bamboo charcoal.
[0047] (S.5) 30 g of the composite bamboo charcoal, 1 g of naphthalenesulfonate formaldehyde condensate and 5 g of fatty alcohol polyoxyethylene ether are mixed at high speed to obtain a composite bamboo charcoal dispersion.
[0048] Example 4 A composite bamboo charcoal dispersion for viscose fiber, the preparation method of which is as follows: (S.1) Add 5 g of sodium dodecylbenzene sulfonate to 60 g of deionized water, mix at 500 rpm, add 35 g of bamboo charcoal, stir at 1000 rpm for 1 hour, grind in a grinder for 2 hours, and use a laser particle size analyzer to measure the particle size D90 < 0.3 μm to obtain nano bamboo charcoal slurry.
[0049] (S.2) The pH value of the nano bamboo charcoal slurry is adjusted to 9 with 1 mol / L sodium hydroxide solution, the temperature is raised to 55°C, 0.5 mol / L silver nitrate is added, the temperature is raised to 120°C for hydrothermal reaction for 10 hours, and the amount of silver nitrate solution added is 2% of the bamboo charcoal in terms of silver oxide.
[0050] (S.3) Then the temperature is lowered to 70°C, 1 mol / L sodium silicate solution is added, and the reaction is carried out for 1 hour. The amount added is 3% of the bamboo charcoal in terms of silicon dioxide.
[0051] (S.4) The precipitate is washed with deionized water for multiple times, filtered, and dried to obtain composite bamboo charcoal.
[0052] (S.5) 30 g of the composite bamboo charcoal, 1 g of naphthalenesulfonate formaldehyde condensate and 5 g of fatty alcohol polyoxyethylene ether are mixed at high speed to obtain a composite bamboo charcoal dispersion.
[0053] Example 5 A composite bamboo charcoal dispersion for viscose fiber, the preparation method of which is as follows: (S.1) Add 5 g of sodium dodecylbenzene sulfonate to 60 g of deionized water, mix at 500 rpm, add 35 g of bamboo charcoal, stir at 1000 rpm for 1 hour, grind in a grinder for 2 hours, and use a laser particle size analyzer to measure the particle size D90 < 0.3 μm to obtain nano bamboo charcoal slurry.
[0054] (S.2) The pH value of the nano bamboo charcoal slurry is adjusted to 9 with 1 mol / L sodium hydroxide solution, the temperature is raised to 55°C, 1 mol / L zinc sulfate and 0.5 mol / L magnesium sulfate solution are added, the temperature is raised to 140°C for hydrothermal reaction for 12 hours, the amount of zinc sulfate solution added is 2% of the bamboo charcoal based on zinc oxide, and the amount of magnesium sulfate solution added is 0.5% of the bamboo charcoal based on magnesium oxide.
[0055] (S.3) Then the temperature is lowered to 70°C, 1 mol / L sodium silicate solution is added, and the reaction is carried out for 1 hour. The amount added is 3% of the bamboo charcoal in terms of silicon dioxide.
[0056] (S.4) The precipitate is washed with deionized water for multiple times, filtered, and dried to obtain composite bamboo charcoal.
[0057] (S.5) 30 g of the composite bamboo charcoal, 1 g of naphthalenesulfonate formaldehyde condensate and 5 g of fatty alcohol polyoxyethylene ether are mixed at high speed to obtain a composite bamboo charcoal dispersion.
[0058] Example 6 A composite bamboo charcoal dispersion for viscose fiber, the preparation method of which is as follows: (S.1) Add 5 g of sodium dodecylbenzene sulfonate to 65 g of deionized water, mix at 500 rpm, add 30 g of bamboo charcoal, stir at 1000 rpm for 1 hour, grind in a grinder for 2 hours, and use a laser particle size analyzer to measure the particle size D90 < 0.3 μm to obtain nano bamboo charcoal slurry.
[0059] (S.2) The pH value of the nano bamboo charcoal slurry is adjusted to 9 with 1 mol / L sodium hydroxide solution, and the temperature is raised to 55°C. 1 mol / L tetrabutyl titanate and 0.5 mol / L magnesium sulfate solution are added, and the temperature is raised to 130°C for hydrothermal reaction for 10 hours. The amount of tetrabutyl titanate solution added is 2% of the bamboo charcoal calculated as titanium dioxide, and the amount of magnesium sulfate solution added is 1% of the bamboo charcoal calculated as magnesium oxide.
[0060] (S.3) Then the temperature is lowered to 70°C, 1 mol / L sodium silicate solution is added, and the reaction is carried out for 1 hour. The amount added is 3% of the bamboo charcoal in terms of silicon dioxide.
[0061] (S.4) The precipitate is washed with deionized water for multiple times, filtered, and dried to obtain composite bamboo charcoal.
[0062] (S.5) 30 g of the composite bamboo charcoal, 1 g of naphthalenesulfonate formaldehyde condensate and 5 g of fatty alcohol polyoxyethylene ether are mixed at high speed to obtain a composite bamboo charcoal dispersion.
[0063] Example 7 A composite bamboo charcoal dispersion for viscose fiber, the preparation method of which is as follows: (S.1) Add 3 g of sodium dodecylbenzene sulfonate to 67 g of deionized water, mix at 500 rpm, add 30 g of bamboo charcoal, stir at 1000 rpm for 1 hour, grind in a grinder for 2 hours, and use a laser particle size analyzer to measure the particle size D90 < 0.3 μm to obtain nano bamboo charcoal slurry.
[0064] (S.2) The pH value of the nano bamboo charcoal slurry is adjusted to 9 with 1 mol / L sodium hydroxide solution, the temperature is raised to 55°C, 1 mol / L copper sulfate and 0.5 mol / L aluminum sulfate solution are added, the temperature is raised to 120°C for hydrothermal reaction for 10 hours, the amount of copper sulfate solution added is 2% of the bamboo charcoal calculated as titanium dioxide, and the amount of aluminum sulfate solution added is 0.1% of the bamboo charcoal calculated as magnesium oxide.
[0065] (S.3) Then the temperature is lowered to 70°C, 1 mol / L sodium silicate solution is added, and the reaction is carried out for 1 hour. The amount added is 3% of the bamboo charcoal in terms of silicon dioxide.
[0066] (S.4) The precipitate is washed with deionized water for multiple times, filtered, and dried to obtain composite bamboo charcoal.
[0067] (S.5) 30 g of the composite bamboo charcoal, 1 g of naphthalenesulfonate formaldehyde condensate and 5 g of fatty alcohol polyoxyethylene ether are mixed at high speed to obtain a composite bamboo charcoal dispersion.
[0068] Example 8 A composite bamboo charcoal dispersion for viscose fiber, the preparation method of which is as follows: (S.1) Add 3 g of sodium dodecylbenzene sulfonate to 67 g of deionized water, mix at 500 rpm, add 30 g of bamboo charcoal, stir at 1000 rpm for 1 hour, grind in a grinder for 2 hours, and use a laser particle size analyzer to measure the particle size D90 < 0.3 μm to obtain nano bamboo charcoal slurry.
[0069] (S.2) The pH value of the nano bamboo charcoal slurry is adjusted to 9 with 1 mol / L sodium hydroxide solution, the temperature is raised to 55°C, 1 mol / L zinc sulfate solution is added, the temperature is raised to 120°C for hydrothermal reaction for 10 hours, and the amount of zinc sulfate solution added is 2% of the bamboo charcoal based on zinc oxide.
[0070] (S.3) Then the temperature is lowered to 70°C, 1 mol / L sodium silicate solution is added, and the reaction is carried out for 1 hour. The amount added is 3% of the bamboo charcoal in terms of silicon dioxide.
[0071] (S.4) The precipitate is washed with deionized water for multiple times, filtered, and dried to obtain composite bamboo charcoal.
[0072] (S.5) The above 20% composite bamboo charcoal, 1% naphthalenesulfonate formaldehyde condensate, and 1% fatty alcohol polyoxyethylene ether are mixed by high-speed stirring to obtain a composite bamboo charcoal dispersion.
[0073] Example 9 A composite bamboo charcoal dispersion for viscose fiber, the preparation method of which is as follows: (S.1) Add 3 g of sodium dodecylbenzene sulfonate to 67 g of deionized water, mix at 500 rpm, add 30 g of bamboo charcoal, stir at 1000 rpm for 1 hour, grind in a grinder for 2 hours, and use a laser particle size analyzer to measure the particle size D90 < 0.3 μm to obtain nano bamboo charcoal slurry.
[0074] (S.2) The pH value of the nano bamboo charcoal slurry is adjusted to 9 with 1 mol / L sodium hydroxide solution, the temperature is raised to 55°C, 1 mol / L zinc sulfate solution is added, the temperature is raised to 120°C for hydrothermal reaction for 10 hours, and the amount of zinc sulfate solution added is 2% of the bamboo charcoal based on zinc oxide.
[0075] (S.3) Then the temperature is lowered to 70°C, 1 mol / L sodium silicate solution is added, and the reaction is carried out for 1 hour. The amount added is 3% of the bamboo charcoal in terms of silicon dioxide.
[0076] (S.4) The precipitate is washed with deionized water for multiple times, filtered, and dried to obtain composite bamboo charcoal.
[0077] (S.5) 45 g of the composite bamboo charcoal, 5 g of naphthalenesulfonate formaldehyde condensate and 8 g of fatty alcohol polyoxyethylene ether are mixed at high speed to obtain a composite bamboo charcoal dispersion.
[0078] Comparative Example 1 A composite bamboo charcoal dispersion for viscose fiber, the preparation method of which is as follows: (S.1) Add 3 g of sodium dodecylbenzene sulfonate to 67 g of deionized water, mix at 500 rpm, add 30 g of bamboo charcoal, stir at 1000 rpm for 1 hour, grind in a grinder for 2 hours, and use a laser particle size analyzer to measure the particle size D90 < 0.3 μm to obtain nano bamboo charcoal slurry.
[0079] (S.2) The pH value of the nano bamboo charcoal slurry is adjusted to 9 with 1 mol / L sodium hydroxide solution, the temperature is raised to 55°C, 1 mol / L zinc sulfate solution is added, the temperature is raised to 120°C for hydrothermal reaction for 10 hours, and the amount of zinc sulfate solution added is 2% of the bamboo charcoal based on zinc oxide.
[0080] (S.3) The precipitate is washed with deionized water for multiple times, filtered, and dried to obtain composite bamboo charcoal.
[0081] (S.4) 30 g of the composite bamboo charcoal, 1 g of naphthalenesulfonate formaldehyde condensate and 5 g of fatty alcohol polyoxyethylene ether are mixed at high speed to obtain a composite bamboo charcoal dispersion.
[0082] Comparative Example 2 A composite bamboo charcoal dispersion for viscose fiber, the preparation method of which is as follows: (S.1) Add 3 g of sodium dodecylbenzene sulfonate to 67 g of deionized water, mix at 500 rpm, add 30 g of bamboo charcoal, stir at 1000 rpm for 1 hour, grind in a grinder for 2 hours, and use a laser particle size analyzer to measure the particle size D90 < 0.3 μm to obtain nano bamboo charcoal slurry.
[0083] (S.2) The nano bamboo charcoal slurry is heated to 70°C, and 1 mol / L sodium silicate solution is added to react for 1 hour. The amount of added sodium silicate is 3% of the bamboo charcoal in terms of silicon dioxide.
[0084] (S.3) The precipitate is washed with deionized water for multiple times, filtered, and dried to obtain composite bamboo charcoal.
[0085] (S.4) 30 g of the composite bamboo charcoal, 1 g of naphthalenesulfonate formaldehyde condensate and 5 g of fatty alcohol polyoxyethylene ether are mixed at high speed to obtain a composite bamboo charcoal dispersion.
[0086] Comparative Example 3 A composite bamboo charcoal dispersion for viscose fiber, the preparation method of which is as follows: (S.1) Add 3 g of sodium dodecylbenzene sulfonate to 67 g of deionized water, mix at 500 rpm, add 30 g of bamboo charcoal, stir at 1000 rpm for 1 hour, grind in a grinder for 2 hours, and use a laser particle size analyzer to measure the particle size D90 < 0.3 μm to obtain nano bamboo charcoal slurry.
[0087] (S.2) The pH value of the nano bamboo charcoal slurry is adjusted to 9 with 1 mol / L sodium hydroxide solution, the temperature is raised to 55°C, 1 mol / L zinc sulfate solution is added, the temperature is raised to 120°C for hydrothermal reaction for 10 hours, and the amount of zinc sulfate solution added is 0.5% of the bamboo charcoal based on zinc oxide.
[0088] (S.3) Then the temperature is lowered to 70°C, 1 mol / L sodium silicate solution is added, and the reaction is carried out for 1 hour. The amount added is 3% of the bamboo charcoal in terms of silicon dioxide.
[0089] (S.4) The precipitate is washed with deionized water for multiple times, filtered, and dried to obtain composite bamboo charcoal.
[0090] (S.5) 30 g of the composite bamboo charcoal, 1 g of naphthalenesulfonate formaldehyde condensate and 5 g of fatty alcohol polyoxyethylene ether are mixed at high speed to obtain a composite bamboo charcoal dispersion.
[0091] Comparative Example 4 A composite bamboo charcoal dispersion for viscose fiber, the preparation method of which is as follows: (S.1) Add 3 g of sodium dodecylbenzene sulfonate to 67 g of deionized water, mix at 500 rpm, add 30 g of bamboo charcoal, stir at 1000 rpm for 1 hour, grind in a grinder for 2 hours, and use a laser particle size analyzer to measure the particle size D90 < 0.3 μm to obtain nano bamboo charcoal slurry.
[0092] (S.2) The pH value of the nano bamboo charcoal slurry is adjusted to 9 with 1 mol / L sodium hydroxide solution, the temperature is raised to 55°C, 1 mol / L zinc sulfate solution is added, the temperature is raised to 120°C for hydrothermal reaction for 10 hours, and the amount of zinc sulfate solution added is 10% of the bamboo charcoal based on zinc oxide.
[0093] (S.3) Then the temperature is lowered to 70°C, 1 mol / L sodium silicate solution is added, and the reaction is carried out for 1 hour. The amount added is 3% of the bamboo charcoal in terms of silicon dioxide.
[0094] (S.4) The precipitate is washed with deionized water for multiple times, filtered, and dried to obtain composite bamboo charcoal.
[0095] (S.5) 30 g of the composite bamboo charcoal, 1 g of naphthalenesulfonate formaldehyde condensate and 5 g of fatty alcohol polyoxyethylene ether are mixed at high speed to obtain a composite bamboo charcoal dispersion.
[0096] Comparative Example 5 A composite bamboo charcoal dispersion for viscose fiber, the preparation method of which is as follows: (S.1) Add 3 g of sodium dodecylbenzene sulfonate to 67 g of deionized water, mix at 500 rpm, add 30 g of bamboo charcoal, stir at 1000 rpm for 1 hour, grind in a grinder for 2 hours, and use a laser particle size analyzer to measure the particle size D90 < 0.3 μm to obtain nano bamboo charcoal slurry.
[0097] (S.2) The pH value of the nano bamboo charcoal slurry is adjusted to 9 with 1 mol / L sodium hydroxide solution, the temperature is raised to 55°C, 1 mol / L zinc sulfate solution is added, the temperature is raised to 120°C for hydrothermal reaction for 10 hours, and the amount of zinc sulfate solution added is 2% of the bamboo charcoal based on zinc oxide.
[0098] (S.3) Then the temperature is lowered to 70°C, 1 mol / L sodium silicate solution is added, and the reaction is carried out for 1 hour. The amount added is 0.5% of the bamboo charcoal in terms of silicon dioxide.
[0099] (S.4) The precipitate is washed with deionized water for multiple times, filtered, and dried to obtain composite bamboo charcoal.
[0100] (S.5) 30 g of the composite bamboo charcoal, 1 g of naphthalenesulfonate formaldehyde condensate and 5 g of fatty alcohol polyoxyethylene ether are mixed at high speed to obtain a composite bamboo charcoal dispersion.
[0101] Comparative Example 6 A composite bamboo charcoal dispersion for viscose fiber, the preparation method of which is as follows: (S.1) Add 3 g of sodium dodecylbenzene sulfonate to 67 g of deionized water, mix at 500 rpm, add 30 g of bamboo charcoal, stir at 1000 rpm for 1 hour, grind in a grinder for 2 hours, and use a laser particle size analyzer to measure the particle size D90 < 0.3 μm to obtain nano bamboo charcoal slurry.
[0102] (S.2) The pH value of the nano bamboo charcoal slurry is adjusted to 9 with 1 mol / L sodium hydroxide solution, the temperature is raised to 55°C, 1 mol / L zinc sulfate solution is added, the temperature is raised to 120°C for hydrothermal reaction for 10 hours, and the amount of zinc sulfate solution added is 2% of the bamboo charcoal based on zinc oxide.
[0103] (S.3) Then the temperature is lowered to 70°C, 1 mol / L sodium silicate solution is added, and the reaction is carried out for 1 hour. The amount added is 10% of the bamboo charcoal in terms of silicon dioxide.
[0104] (S.4) The precipitate is washed with deionized water for multiple times, filtered, and dried to obtain composite bamboo charcoal.
[0105] (S.5) 30 g of the composite bamboo charcoal, 1 g of naphthalenesulfonate formaldehyde condensate and 5 g of fatty alcohol polyoxyethylene ether are mixed at high speed to obtain a composite bamboo charcoal dispersion.
[0106] Comparative Example 7 A composite bamboo charcoal dispersion for viscose fiber, the preparation method of which is as follows: (S.1) Add 3 g of sodium dodecylbenzene sulfonate to 67 g of deionized water, mix at 500 rpm, add 30 g of bamboo charcoal, stir at 1000 rpm for 1 hour, grind in a grinder for 2 hours, and use a laser particle size analyzer to measure the particle size D90 < 0.3 μm to obtain nano bamboo charcoal slurry.
[0107] (S.2) The pH value of the nano bamboo charcoal slurry is adjusted to 9 with 1 mol / L sodium hydroxide solution, the temperature is raised to 55°C, 1 mol / L magnesium sulfate solution is added, the temperature is raised to 120°C for hydrothermal reaction for 10 hours, and the amount of magnesium sulfate solution added is 2% of the bamboo charcoal in terms of magnesium oxide.
[0108] (S.3) Then the temperature is lowered to 70°C, 1 mol / L sodium silicate solution is added, and the reaction is carried out for 1 hour. The amount added is 2% of the bamboo charcoal in terms of silicon dioxide.
[0109] (S.4) The precipitate is washed with deionized water for multiple times, filtered, and dried to obtain composite bamboo charcoal.
[0110] (S.5) 30 g of the composite bamboo charcoal, 1 g of naphthalenesulfonate formaldehyde condensate and 5 g of fatty alcohol polyoxyethylene ether are mixed at high speed to obtain a composite bamboo charcoal dispersion.
[0111] The viscose fiber composite bamboo charcoal dispersion prepared in Examples 1-9 and Comparative Examples 1-7 was evenly mixed with the viscose stock solution in a ratio of 2:100, and the mixed spinning stock solution was spun through 30 spinnerets with a diameter of 0.05 mm at a spinning speed of 15 m / min to obtain viscose fiber containing composite bamboo charcoal.
[0112] The deodorization ability of viscose fiber was then tested using the GB / T 33610.1-2019 standard, which uses an instrument to measure the reduction rate of the concentration of odorous chemical components in the air surrounding the textile product. The deodorization performance of textiles refers to the ability to reduce odors in the surrounding air. The main chemical components include ammonia, acetic acid, isovaleric acid, etc. Physical deodorization is to adsorb odors in the air to the surface of the fabric through adsorption, while chemical deodorization eliminates odors through chemical reactions. The test results are shown in Table 1 below.
[0113] Table 1 .
[0114] From the data in the above table, it can be seen that the composite bamboo charcoal dispersion for viscose fiber with good removal rate for odors such as ammonia, acetic acid and isovaleric acid can be obtained by the method in the present application. After comparing Comparative Example 1 and Comparative Example 2 with Example 2, we found that simply loading metal oxides or silicon dioxide on the surface of bamboo charcoal has a low removal efficiency for odor and cannot achieve the purpose of deodorization.
[0115] By comparing Comparative Example 3 with Comparative Example 2, we can see that when the content of metal oxide is too low, its adsorption efficiency for odor is significantly reduced. However, when the content of metal oxide is greatly increased (Comparative Example 4), the adsorption efficiency for odor is not significantly improved. At the same time, its particle size is greatly increased, and the spinneret hole is blocked during the spinning process.
[0116] Similar to metal oxides, when the content of silicon dioxide is too low (Comparative Example 5), its protective effect on metal oxides decreases, thereby significantly reducing the adsorption efficiency of odor. However, when the content of silicon dioxide increases significantly (Comparative Example 6), its particle size also increases significantly, resulting in the phenomenon of spinneret hole clogging during the spinning process.
[0117] In Comparative Example 7, the zinc oxide in Example 2 is replaced by magnesium oxide, which results in a significant decrease in its ability to adsorb odor, indicating that the oxide of the main group metal element alone cannot have a good adsorption effect on odor. In Examples 5-7, the oxide of the transition metal element is compounded with the oxide of the main group metal element. It can be seen that the removal rate of odor is greatly improved after the oxide of the transition metal element is compounded with the oxide of the main group metal element, indicating that the oxide of the transition metal element and the oxide of the main group metal element can produce a synergistic effect.
[0118] The specific embodiments described herein are merely examples of the spirit of the present invention. A person skilled in the art of the present invention may make various modifications or additions to the specific embodiments described or replace them in a similar manner, but this will not deviate from the spirit of the present invention or exceed the scope defined by the appended claims.
Claims
1. A composite bamboo charcoal dispersion for viscose fiber, characterized in that: It includes composite bamboo charcoal, surfactant and water; wherein, The composite bamboo charcoal comprises bamboo charcoal particles, the outside of which is coated with a first coating containing at least one metal oxide, and the outside of the first coating is coated with a second coating composed of silicon dioxide.
2. The composite bamboo charcoal dispersion for viscose fiber according to claim 1, characterized in that: The mass concentration of the composite bamboo charcoal is 20-45%.
3. A composite bamboo charcoal dispersion for viscose fiber according to any one of claim 1, characterized in that: The mass of the first coating body is 1-5% of the mass of the bamboo charcoal particles; The mass of the second coating body is 1-5% of the mass of the bamboo charcoal particles.
4. A composite bamboo charcoal dispersion for viscose fiber according to any one of claims 1 to 3, characterized in that: The metal oxide in the first coating includes at least one or more oxides of transition metal elements.
5. The composite bamboo charcoal dispersion for viscose fiber according to claim 4, characterized in that: The metal oxide in the first coating body further comprises one or more oxides of main group metal elements; The mass ratio of the oxide of the transition metal element to the oxide of the main group metal element is 10:(1-5).
6. A composite bamboo charcoal dispersion for viscose fiber according to claim 4, characterized in that: The oxide of the transition metal element includes any one or more of zinc oxide, titanium dioxide, silver oxide, and copper oxide; The oxide of the main group metal element includes any one or more of magnesium oxide, aluminum oxide and tin oxide.
7. The composite bamboo charcoal dispersion for viscose fiber according to claim 1, characterized in that: The surfactant includes an ionic surfactant and a non-ionic surfactant; The mass concentration of the ionic surfactant is 1-5%, and the mass concentration of the non-ionic surfactant is 1-8%.
8. The composite bamboo charcoal dispersion for viscose fiber according to claim 1, characterized in that: The ionic surfactant includes one or more of sodium dodecylbenzene sulfonate, sodium lignin sulfonate, naphthalene sulfonate formaldehyde condensate, and sodium polycarboxylate; The nonionic surfactant includes one or more of polysorbate, fatty alcohol polyoxyethylene ether, phenylphenol polyoxyethylene ether, castor oil polyoxyethylene ether, and fatty amine polyoxyethylene ether.
9. A method for preparing the composite bamboo charcoal dispersion for viscose fiber as claimed in any one of claims 1 to 8, characterized in that: The following steps are involved: (S.1) dispersing the surfactant and bamboo charcoal particles in deionized water, and wet-grinding to obtain nano bamboo charcoal slurry; (S.2) adjusting the pH of the nano bamboo charcoal slurry to alkaline, adding a metal salt compound, and reacting to coat the surface of the bamboo charcoal particles with a first coating body; (S.3) continuing to add a silicon dioxide precursor to the reaction solution to react, thereby coating the second coating body outside the first coating body; (S.4) washing and drying the generated precipitate to obtain composite bamboo charcoal; (S.5) The composite bamboo charcoal, surfactant and water are mixed evenly and then ground in a grinder to obtain a composite bamboo charcoal dispersion for viscose fiber.
10. Use of the composite bamboo charcoal dispersion for viscose fiber according to any one of claims 1 to 8 in preparing textile fibers.
Citation Information
Patent Citations
Viscose fiber for eliminating bad smell of perspiration and preparation method thereof
CN102839439B
A kind of antibacterial and deodorizing cellulose fiber and preparation method thereof
CN103981588B
Organic zinc antibacterial cellulose fiber and preparation method thereof
CN115896969B
Preparation method of multilayer coated composite heat-insulating filler and application of filler to water-based coating
CN102174281A
Bamboo charcoal fiber fabric and processing method thereof
CN103334315A